Penarikan Paksa Kredit Kendaraan yang Macet oleh Pihak Leasing yang Tidak Mempunyai Sertifikat Fidusia: Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Ruth Anggilani Kaesmetan; Orpa Juliana Nubatonis; Husni Kusuma Dinata (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to find out and analyze the forced withdrawal of bad vehicle loans by leasing parties who do not have a fiduciary certificate based on the decision of the Constitutional Court number 18/PUU-XVII/2019. This research is a normative legal research supported by a legislative approach and a conceptual approach that uses primary legal materials, secondary legal materials and tertiary legal materials collected using literature study methods and case studies after which they are analyzed qualitatively descriptively. The results of the study show that the application of sanctions against leasing companies that forcibly recall vehicles without having a fiduciary certificate is still not fully effective. Although there have been legal provisions that regulate such as Law number 42 of 1999 concerning Fiduciary Guarantees, Civil Code, Consumer Protection Law, and Constitutional Court Decision Number 18/PUU-XVII/2019, in practice there are still many leasing companies that continue to execute guarantees unilaterally without going through the correct legal procedures.